Diagnostic Imaging for Distal Extremity Injuries in Direct Access Physical Therapy: An Observational Study - Michael S Crowell; John S Mason; Jamie B Morris; Max K Dummar; Paul A Kuwik (North American Sports Medicine Institute, 2023)
# Background Military physical therapists practicing direct-access routinely utilize diagnostic imaging and numerous published case reports demonstrate the ability of physical therapists to diagnose and appropriately disposition patients with foot/ankle and wrist/hand fractures. However, no larger cohort studies have explored the utilization of diagnostic imaging by physical therapists to detect fractures. # Hypothesis/Purpose To describe the utilization of diagnostic imaging in foot/ankle and wrist/hand injuries by physical therapists in a direct-access sports physical therapy clinic. # Study Design Retrospective cohort study. # Methods The Agfa Impax Client 6 image viewing software (IMPAX) was searched from 2014 to 2018 for patients with diagnostic imaging ordered for foot/ankle and wrist/hand injuries. The Armed Forces Health Longitudinal Technology Application (AHLTA) electronic medical record was independently reviewed by the principal and co-investigator physical therapists. Data extracted were demographics and elements from the patient history and physical examination. # Results In foot/ankle injuries, physical therapists diagnosed a fracture in 16% of the 177 cases and waited for an average of 3.9 days and 1.3 visits before ordering imaging. In wrist/hand injuries, physical therapists diagnosed a fracture in 24% of the 178 cases and waited for an average of 3.7 days and 1.2 visits before ordering imaging. The time to definitive care from the initial physical therapy evaluation was significantly different (p = 0.04) for foot/ankle fractures (0.6 days) compared to wrist/hand fractures (5.0 days). The Ottawa Ankle Rules demonstrated a negative likelihood ratio (-LR) of 0.11 (0.02, 0.72) and a positive likelihood ratio (+LR) of 1.99 (1.62, 2.44) for the diagnosis of foot/ankle fracture. # Conclusions Physical therapists utilizing diagnostic imaging in a direct-access sports physical therapy clinic diagnosed fractures in similar proportions for foot/ankle and wrist/hand injuries and quickly dispositioned patients to definitive care for those fractures. The diagnostic accuracy of the Ottawa Ankle Rules was similar to previously reported values. # Level of Evidence Level 3.